Respuesta :
because these are roots of cubic function so just multiplie
(x-sqrt6)(x+sqrt6)(x+3) = ? and will get the right cubic function easy
(x-sqrt6)(x+sqrt6)(x+3) = ? and will get the right cubic function easy
Answer: The cubic function will be
[tex]x^3+3x^2-6x-18[/tex]
Step-by-step explanation:
Since we have given that
the roots are
[tex]\sqrt{6},-\sqrt{6},-3[/tex]
Since it has three roots , so it is a cubic function.
The cubic function is given by
[tex](x-\sqrt{6})(x+\sqrt{6})(x-(-3))\\\\=(x^2-(\sqrt{6})^2)(x+3)\\\\=(x^2-6)(x+3)\\\\=x^2(x+3)-6(x+3)\\\\=x^3+3x^2-6x-18[/tex]
So, the cubic function will be
[tex]x^3+3x^2-6x-18[/tex]